Effectiveness of Low Level Laser Therapy on Pain and Functional Status in Ankylosing Spondylitis - AKYÜZ, GÜLSEREN DERYA; GÜNDÜZ, OSMAN HAKAN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2012)
Objective: The aim of this study was to evaluate the effects of low-level laser therapy (LLLT) on pain, functional status and disease activity in patients with ankylosing spondylitis (AS). Materials and Methods: A randomized, double-blind, placebo-controlled trial was performed on 37 patients. Group 1 (n=19) was treated with LLLT for 10 sessions (1.2J, 30 mW), group 2 received placebo laser. LLLT was applied on the L3 to S1 supraspinous ligaments and sacroiliac joints bilaterally with a skin-contact method. Evaluation parameters were Visual Analogue Scale (VAS), at rest and during movements, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), and the Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire. Results: Compared with the pre-therapy, LLLT group showed significant improvement in VAS (p<0.05), ASQoL (p<0.01) and BASDAI (p<0.001) scores during movement at the end of the treatment and at the second month (p<0.05). However, there was no statistically significant difference between treatment and placebo groups. Conclusion: This is the first study to assess the effects of LLLT in patients with AS. The results show LLLT seemed to improve pain and functional status in patients with AS.
Keywords: Low-level laser therapy; low back pain; inflammation; ankylosing spondylitis; LOW-BACK-PAIN; ENDOGENOUS OPIOID ANALGESIA; LOW-POWER LASER; CONTROLLED-TRIAL; DOUBLE-BLIND; INFLAMMATION; EFFICACY; RATS; IRRADIATION; MANAGEMENT